Association between visceral/subcutaneous adipose tissue ratio and plasma inflammatory markers and score for cardiovascular risk prediction in a Brazilian cohort: Pró-Saúde Study - Pereira-Manfro,W.F. (2021)
Visceral adipose tissue (VAT) is associated with various metabolic disorders, and adipokines, secreted by adipose tissue, are involved in their pathogenesis. This study investigated associations between VAT/subcutaneous adipose tissue (SAT) ratio, inflammatory markers, and cardiovascular (CV) risk-score in adults. Plasma levels of adipokines, plasma lipid profile, blood pressure, and body composition (using dual-emission x-ray absorptiometry) were determined. CV risk-score based on the American College of Cardiology and the American Heart Association (ACC/AHA) score was calculated in a sample of 309 Brazilian civil servants aged <60 years. Participants' VAT/SAT ratio were categorized into quartiles. Among males, plasma leptin (2.8 ng/mL) and C reactive protein (CRP) (0.2 mg/dL) (P<0.05) levels were higher at P75 and P50 than P5, and the highest calculated CV risk-score was observed at P75 (7.1%). Among females, higher plasma adiponectin levels were observed at P25 (54.3 ng/mL) compared with P75 (36 ng/mL) (P<0.05). Higher plasma CRP levels were observed at P75 (0.4 mg/dL) compared with P5 (0.1 mg/dL) (P<0.05). Higher CV risk-score was observed at P75 (2.0%) compared with P5 (0.7%). In both sexes, VAT and VAT/SAT ratio were directly associated with plasma leptin, CRP, and CV risk-score, and inversely associated with adiponectin; SAT was directly associated with plasma leptin and CRP (P<0.01); interleukin (IL)-10 and CRP were directly associated with adiponectin and leptin, respectively (P<0.05). Among men only, IL-10 (inversely) and CRP (directly) were associated with CV risk-score (P=0.02). Our results strengthened the relevance of the VAT/SAT ratio in cardiovascular risk.